2014
DOI: 10.1176/appi.ps.201300290
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatrists’ Judgments About Antipsychotic Benefit and Risk Outcomes and Formulation in Schizophrenia Treatment

Abstract: Psychiatrists favored treatments that primarily improve positive symptoms. Choice of formulation became more important as likely adherence declined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…The findings of this study were similar to those of other published studies in which respondents valued improvements in social functioning and positive symptoms more than improvement in negative symptoms and avoidance of side effects (8,9). A related study in which the authors assessed psychiatrist judgments about medications' benefits and risks showed that the psychiatrists and patients had several results in common (21,22). Like patients, psychiatrists showed that positive symptoms were their dominant concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study were similar to those of other published studies in which respondents valued improvements in social functioning and positive symptoms more than improvement in negative symptoms and avoidance of side effects (8,9). A related study in which the authors assessed psychiatrist judgments about medications' benefits and risks showed that the psychiatrists and patients had several results in common (21,22). Like patients, psychiatrists showed that positive symptoms were their dominant concern.…”
Section: Discussionmentioning
confidence: 99%
“…This survey was developed in conjunction with a similar instrument targeted to physicians (21,22). Applying an approach based in multicriteria decision analysis and the Benefit-Risk Action Team (BRAT) framework (23,24), we conducted written and telephone interviews with expert academic psychiatrists and assessed product inserts and publications to determine what attributes to include in the survey.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Detailed descriptions of the two trials have been published 20,21. These surveys were adapted from versions used in pilot studies conducted with patients and physicians sampled from online panels 18,19…”
Section: Methodsmentioning
confidence: 99%
“…Previous preference studies in schizophrenia, performed with online panels of psychiatrists and patients, demonstrated that schizophrenia patients were capable of completing such surveys,16,17 and that both physicians and patients place greater importance on improvements in positive symptoms than on improvements in negative symptoms or in avoiding treatment-related AEs (weight gain, extrapyramidal symptoms [EPS], hyperglycemia, and hyperprolactinemia) 18,19. Patient adherence to oral antipsychotics was identified as an important factor in the assessment of oral versus injectable medicine formulations 2022.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation